Estudio comparativo sobre el efecto antihipertensivo del citrullus lanatus (sandía) y enalapril en rattus rattus var albinus - Rodríguez Ybañez, Roberto Moisés (2014)
Compare the effect of Citrullus lanatus (watermelon) with enalapril on arterial hypertension in Rattus rattus var albinus. Material and Method: A randomized study was realized. I worked with 39 Rattus rattus var albinus male. The specimens were divided in 3 groups G1, G2 y G3. They were put under stage of preparation by 1 week, After basal determination, arterial hypertension was induced using L-NAME 50 mg/kg/d VO and four weeks after the treatment was initiated with fruit juice 5ml /kg/d VO, enalapril 25 mg/ kg/ d VO and sterile water 5ml/Kg/d VO, respectively. Arterial pressure was measured on days 31, 34 and 38. Was applied the Test of Variance Analysis and Test of Duncan. Results: Citrullus lanatus (watermelon) in the systolic blood pressure (SBP), diastolic blood pressure (DBP) and median blood pressure (MBP) starting the first day of treatment was found: 148.2 ± 2.12, 109.1 ± 2.78 and 122.1 ± 2.12, respectively compared to171.1 ± 4.35, 130.2 ± 4.16 and 143.8 ± 3.60 of the L-NAME + sterile water group (p < 0,05), respectively. Enalapril in the systolic blood pressure (SBP), diastolic blood pressure (DBP) and median blood pressure (MBP) starting the first day of treatment was found: 138.8 ± 2.89, 95.8 ± 3.49 y 110.1 ± 2.53 respectively compared to the L-NAME + sterile water group (p < 0,05). And finally enalapril in SBP, DBP, and MAP starting the first day of treatment was found: 138.8 ± 2.89, 95.8 ± 3.49 and 110.1 ± 2.53, respectively, compared to 148.2 ± 2.12, 109.1 ± 2.78 and 122.1 ± 2.12 of the Citrullus lanatus (watermelon) group (p < 0.05). Conclusions: The administration of Citrullus lanatus produced a statistically significant reduction of systolic blood pressure (SBP), diastolic (DBP) and median (MBP) in comparison with the group that received L-NAME and sterile water. The reduction produced by Citrullus lanatus (watermelon) in SBP, DBP, and MAP is less to enalapril in hypertensive rats